Clear Aligners and Miniscrews in a Scissor Bite Adult Treatment - Teresa Pinho; Duarte Rocha; Sara Gonçalves; Maria Luís Martins (Case Reports in Dentistry)
Scissor bite does not correct spontaneously. It gradually worsens by overeruption, negatively affecting masticatory function. It is intended with this manuscript to evaluate the different treatment strategies to correct this malocclusion in adult patients, exploring treatment with clear aligners, bite ramps, and MS (miniscrews), especially in this case of a patient with unilateral right scissor bite, with high dental compensation in the three planes of space, asymmetrical sagittal dental position, overeruption on the scissor bite condition, and a high mandibular arch constriction and maxillary expansion. A comprehensive literature research was performed from 2002 until March 2023. PubMed and BVS databases were used, with the following keywords: “scissor bite OR brodie bite” AND “malocclusion” AND “treatment OR correction OR therapeutics”. Since correcting skeletal asymmetries after the growth completion is challenging, adult patient cases often involve a combined orthodontic-surgical approach. In the present clinical case, the severe limitations to decompensating tooth positions for a surgical treatment, with the necessity to perform lower asymmetric extraction and a must longer orthodontic treatment, were the major reasons to avoid the surgical approach, after the scissor bite correction. In spite of this, the efficiency of the clear aligners and auxiliaries like bite ramps, MS, and elastics in successfully correcting a complex scissor bite in an adult patient was demonstrated, with significant esthetic and functional commitment, demonstrated by the case reliability PAR (peer assessment rating) index.